Analisis Bahaya Longsor di Kecamatan Padalarang Kabupaten Bandung Barat Berbasis Sistem Informasi Geografis: Geographic Information System Based Analysis of Landslide Hazards in Padalarang Sub-district, West Bandung Regency - Rahmawati, Septi Sri; Khoirullisan, Ahmad Rif’an; Sarastika, Tiara; Nurcholis, Mohammad (Universitas Hasanuddin, 2023)
Indonesia is characterized by a diverse topography and low to very high rainfall intensity. In addition, the population density in fertile Indonesian hilly areas is also increasing. These conditions translate to high potential for landslide hazard in Indonesia with threats of loss ranging from economic, social, to fatalities. One of the areas with a high level of landslide hazard is Padalarang Subdistrict, West Bandung Regency, West Java Province. The purpose of this research is to identify the landslide hazard in Padalarang Subdistrict, West Bandung Regency. Geographic Information System Analysis was used in this study by using an overlay technique presented on the map. The analytical method used was a survey-exploratory analysis with descriptive analysis techniques. The results showed that the landslide hazard in Padalarang Subdistrict could be divided into three categories; having landslide hazard in the north, having landslide potential in the north to the west and southeast, and having no landslide hazard in the central to southern parts which are alluvial plains. Analysis of the landslide hazard in Padalarang Subdistrict provided a spatial picture so that it could be potentially employed to be part of disaster mitigation to minimize material and non-material losses.